(untitled) (Confluenţe Bibliologice, 2026)
The article is about the life and work of Gheorghe Esanu, popular music singer. His repertoire was vast, interpreting successfully popular songs, ballads as well as songs of Moldovan composers. He scored a separate chapter in the history of national musical culture.